No increased DNA damage in peripheral lymphocytes of sewage workers as evaluated by alkaline single cell gel electrophoresis. Issue 7 (July 1997) - Friis, L; Vaghef, H; Edling, C; Hellman, B
Abstract : OBJECTIVES: To study whether sewage workers are exposed to genotoxic substances. An increased risk of cancers among sewage workers has been noted. If this increased risk is due to an exposure to genotoxic agents, primarily DNA damage could be used as a biological marker of exposure. METHODS: In a cross sectional study, DNA damage in peripheral lymphocytes from 35 sewage workers and 30 controls was compared with alkaline single cell gel electrophoresis, a technique for detecting single strand breaks and alkali labile sites in DNA. The controls were selected from among municipal workers matched for age and smoking habit. Information about occupational exposures and possible confounders was collected by means of a questionnaire. RESULTS: No increase in DNA damage was found among the sewage workers when compared with the unexposed controls. CONCLUSIONS: The failure to detect increased damage to DNA in peripheral lymphocytes by alkaline single cell gel electrophoresis suggests that the sewage workers studied here were not exposed to genotoxic agents to a greater extent than other municipal workers. It may be, however, that the lymphocyte is not the appropriate target cell to study, or that sewage workers are exposed to carcinogens which do not damage the genetic material.